Care of general practice patients preceding and following a suicide attempt: observational study in Flemish general practices. - Nicole Boffin; Viviane Van Casteren; Karin De Ridder (BMJ Open, 2019)
OBJECTIVES: First, to examine general practitioner (GP) knowledge about the care (needs) of their patients; second, to examine the quality of GP follow-up care; third, to examine the transmission of patient care information from hospitals/emergency services (ES) to GPs. SETTING: 105 general practices from the representative Belgian Network of Sentinel General Practices (SGP) in Flanders, the largest region of Belgium, during 2013-2016. PARTICIPANTS: 245 suicide attempts by regular patients. OUTCOMES MEASURES: Ten care-related measures, including three indicators of quality of follow-up care, were based on data reported by the SGP on structured forms at baseline and at two follow-up points in time. RESULTS: As for GP knowledge, 10.5% of SGP failed to report whether suicidal risk was noticed in patients seen in the month preceding the attempt; 9.0% whether there were previous attempts; 22.5% whether the patient was receiving mental health treatment at follow-up and 22.0% whether suicidal behaviour was repeated at follow-up. Relatively more patients≥65 years had no suicide risk evaluation (OR 3.54; 95% CI 1.11 to 11.26). As for quality of follow-up care, there was a GP-patient contact following 90.5% of the attempts, follow-up appointments were planned following 43.4% of the attempts and there was a GP contact with patient proxies following 62.8% of the attempts. Patient age ≥65 years (OR 4.09; 95% CI 1.79 to 9.33), a recent GP-patient contact preceding the attempt (OR 1.97; 95% CI 1.13 to 3.43), depression of patient (OR 1.96; 95% CI 1.14 to 3.37) and a suburban SGP area (OR 2.34; 95% CI 1.13 to 4.82) were determinants of an increased quality of care sum. GPs received patient care information from a hospital (ES) for 67.8% of eligible attempts, with SGP practice location being a determinant. CONCLUSIONS: GPs are highly involved in the care of suicide attempters but there is room for improvement, also in informational continuity from hospital (ES) to GPs.